2018
DOI: 10.18203/2394-6040.ijcmph20183969
|View full text |Cite
|
Sign up to set email alerts
|

A study on the immunisation status and the factors responsible for incomplete immunization amongst children of age group 0-12 months coming to a tertiary care hospital (IGIMS)

Abstract: Background: Vaccines are safe, simple and one of the most cost-effective way to save and improve the lives of children. The World Health Organization launched the Global Programme of Immunization in 1974 and Government of India launched the same in India on 1st January, 1978, with a view to provide protection to the children against disease and to reduce infant mortality rate.Methods: A hospital based cross sectional study was carried out in the immunization clinic of a tertiary care hospital (IGIMS) of Patna … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
2
3
0
Order By: Relevance
“…and kurane et al 12 .The various other reasons for defaulting were family problems, lack of initiative, bad experiences and fear of adverse events following immunization . Similar findings were seen in various studies done in various parts of the country [13][14][15][16][17][18][19] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…and kurane et al 12 .The various other reasons for defaulting were family problems, lack of initiative, bad experiences and fear of adverse events following immunization . Similar findings were seen in various studies done in various parts of the country [13][14][15][16][17][18][19] .…”
Section: Discussionsupporting
confidence: 91%
“…A total of 247 children were studied, of which 153(61.94%) were fully immunized, and 94(38.05%) were partially immunized and there was no child who was unimmunized. A study done by Shivani sinha et al 13 showed 40% children being fully vaccinated. 41.4% of children were fully vaccinated, 44.8% were partially vaccinated and 13.8% unimmunised in a study done by Sathish Chandra et al 14 .…”
Section: Discussionmentioning
confidence: 96%
“…13,18,19 Also it is higher than that in NFHS 4 district data for Agra. 20 Urban predominance similar to the current study was also observed by Sinha et al 21 Our study found low immunization coverage with 40.2% full immunization and 42.9% partial immunization. This is in congruence with studies by Sinha et al, Manglik et al and Agrawal et al who noted low full immunization at 40.33%, 46.52% and 41.4% respectively.…”
Section: Discussionsupporting
confidence: 89%
“…This is in congruence with studies by Sinha et al, Manglik et al and Agrawal et al who noted low full immunization at 40.33%, 46.52% and 41.4% respectively. [21][22][23] However, it is lower than the district average of full immunization for Agra as per NFHS 4 which is at 60.9%. 20 This may be due to limited sample size and constrained single site used for sampling.…”
Section: Discussionmentioning
confidence: 87%
“…The poor coverage of full immunisation (44%) and timely immunisation among our sample in this analysis echoes findings from other northern and central Indian states, showcasing a widespread shortcoming of the Indian health system. 36 We found that timeliness was highest for birth vaccines-around four out of five children were administered these on time, likely because these are administered at the facility before the mother and child are discharged postpartum. However, the percentage of children receiving timely vaccinations decreased as they grew.…”
Section: Determinants Of Immunisation Coveragementioning
confidence: 81%